Molybdenum disulfide particles and lubricating composition
Patent Information
- Application Number
- KR1020237031437
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-24
- Filing Date
- 2021-10-21
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2041-10-21
Smart Images

Figure R1020237031437_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to molybdenum disulfide particles and a lubricating composition.
[0002] The present application claims priority based on Japanese Patent Application No. 2021-050478 filed in Japan on March 24, 2021, and incorporates the contents thereof herein. Background Technology
[0003] Molybdenum disulfide is known as a lubricant for reducing frictional wear, mainly in the automotive industry, and is used in various countries, particularly as a liquid lubricant such as engine oil. Molybdenum sulfides, represented by molybdenum disulfide (MoS2), are known to be applied, for example, as lubricants included in solid sliding members or grease (see Patent Documents 1–3).
[0004] Inexpensive powders made by grinding natural molybdenum disulfide minerals have a size on the order of μm and a very high specific gravity of about 5, so they have the drawback of having a small effect per weight of addition. In addition, molybdenum disulfide, which is generally used as a lubricant, is a hexagonal solid lubricant and is known to have only 2H (hexagonal) as a crystal structure. Prior art literature
[0005] Japanese Patent Publication No. 2017-115920, Japanese Patent Publication No. 2013-144758, Japanese Patent No. 6614471 The problem to be solved
[0006] The nano-sized molybdenum disulfide particles, which are proprietary products of the applicant, have a unique 3R (rhombohedral) structure in addition to 2H as their crystal structure. According to this technology, by manufacturing molybdenum disulfide particles using the "nm-sized molybdenum trioxide microparticles" of the technology owned by the applicant as a raw material, it is possible to synthesize "molybdenum disulfide containing a 3R structure and having lightness advantageous for nanoscale and representative area," which is difficult to achieve through the crushing of optical products or the synthesis of general-purpose molybdenum trioxide.
[0007] However, in this nm-sized molybdenum disulfide, the actual full width at half maximum of the XRD peak is significantly larger than the full width at half maximum of the peak predicted from the particle size, so it is not possible to quantify the state of the crystal, such as the crystallite size or the abundance ratio of the 2H crystal structure and the 3R crystal structure. Therefore, there is a problem in that it is difficult to determine whether the crystallite size or the above abundance ratio changes depending on differences in manufacturing conditions, and furthermore, whether it affects the frictional properties in application evaluation.
[0008] The present invention aims to provide molybdenum disulfide particles and a lubricating composition having appropriate particle size and crystallite size and capable of improving friction characteristics. means of solving the problem
[0009] The inventors, focusing on the heating conditions during the manufacture of the molybdenum disulfide particles, conducted further analysis and found that (1) the change in XRD peak intensity or half-width changes due to changes in heating conditions allows for the quantitative determination of changes in crystallite size and crystallinity of the 2H crystal structure and 3R crystal structure based on these changes, and (2) the ratio of the 2H crystal structure and 3R crystal structure changes due to the same heating conditions, and the ratio can be quantified using Rietveld analysis software (manufactured by Malvern Analytical, Highscore Plus, hereinafter referred to as "Extended Rietveld Analysis") that can consider crystallite size, and as a result, (3) the friction coefficient changes in the friction test in an oil dispersion system, and the friction characteristics can be improved by quantifying the friction coefficient.
[0010] In addition, as a result of the extended Rietveld analysis above, it was found that depending on the heating conditions, the 2H crystal structure of the molybdenum disulfide particles consists of a single crystal phase having a relatively small crystallite size, a crystal phase having a larger crystallite size compared to the single crystal phase (first crystal phase), and a low crystallite phase having a smaller crystallite size compared to the single crystal phase (second crystal phase).
[0011] That is, the present invention provides the following configuration.
[0012] [1] Molybdenum disulfide has a 2H crystal structure and a 3R crystal structure,
[0013] The abundance of the above 3R crystal structure in the crystalline phase of molybdenum disulfide is 10% or more, and
[0014] Molybdenum disulfide particles having a crystallite size of 1 nm or more and 150 nm or less, calculated by extended Rietveld analysis based on the formula L=Kλ / (βcosθ) using a profile obtained from powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source.
[0015] (In the above formula, K is a device constant depending on the XRD optical system (incident side and detector side) and settings, L is the size of the crystallite [m], λ is the wavelength of the measured X-ray [m], β is the full width at half maximum [rad], and θ is the Bragg angle of the diffraction line [rad])
[0016] [2] The molybdenum disulfide particles described in [1], wherein the 3R crystal structure obtained by extended Rietveld analysis is composed of crystal phases having crystallite sizes of 5 nm or more and 50 nm or less calculated based on the analysis formula.
[0017] [3] The 2H crystal structure obtained by the extended Rietveld analysis is composed of a single crystal phase having a crystallite size calculated based on the analysis formula, and
[0018] Molybdenum disulfide particles described in [1], wherein the crystallite size of the crystal phase of the above 2H crystal structure is 1 nm or more and 20 nm or less.
[0019] [4] Molybdenum disulfide particles described in [3], wherein the ratio of the 2H crystal structure and the 3R crystal structure obtained by extended Rietveld analysis using the profile obtained from the XRD above is 10:90 to 90:10.
[0020] [5] The 2H crystal structure obtained by extended Rietveld analysis is composed of a first crystal phase having a crystallite size calculated based on the analysis formula and a second crystal phase having a crystallite size smaller than that of the first crystal phase.
[0021] Molybdenum disulfide particles described in [1], wherein the crystallite size of the second crystal phase of the above 2H crystal structure is 1 nm or more and 20 nm or less.
[0022] [6] Molybdenum disulfide particles described in [5], wherein the ratio of the first crystal phase of the 2H crystal structure, the 3R crystal structure, and the second crystal phase of the 2H crystal structure obtained by extended Rietveld analysis using the profile obtained from the XRD above is 30~10:10~70:80~15.
[0023] [7] Molybdenum disulfide particles described in any one of [1] to [6], wherein the molybdenum disulfide particles contain an amorphous phase and the amorphous phase of the molybdenum disulfide particles has an abundance of 5% or more.
[0024] [8] Molybdenum disulfide particles described in any one of [1] to [7], wherein the ratio (I / II) of the intensity of the peak attributable to Mo-S and the intensity of the peak attributable to Mo-Mo is greater than 1.0 in the broad-spectrum X-ray absorption microstructure (EXAFS) profile of the K absorption group of molybdenum.
[0025] [9] Media glasses of molybdenum disulfide particles obtained by dynamic light scattering method D 50 Molybdenum disulfide particles described in any one of [1] to [8] above, having a diameter of 10 nm or more and 1000 nm or less.
[0026]
[10] Molybdenum disulfide particles described in any one of [1] to [9], having a specific surface area of 10 m² / g or more as measured by the BET method.
[0027]
[11] A lubricating composition containing molybdenum disulfide particles described in any one of [1] to
[10] above, a base oil composed of one or more types of mineral oil, synthetic oil and partially synthetic oil, and additives such as a dispersant.
[0028]
[12] The lubricating composition described in
[11] , containing 0.0001 mass% or more and 10 mass% or less of the molybdenum disulfide particles for every 100 mass% of the total mass of the lubricating composition.
[0029]
[13] A lubricating composition described in
[11] or
[12] , further containing organometallic complex particles.
[0030]
[14] A lubricating composition described in
[13] containing 0.0001 mass% or more and 10 mass% or less of the organometallic complex particles for every 100 mass% of the total mass of the lubricating composition. Effects of the invention
[0031] According to the present invention, molybdenum disulfide particles and a lubricating composition having appropriate particle size, crystallite size, and crystal structure can be provided to improve friction characteristics. Brief explanation of the drawing
[0032] FIG. 1 is a schematic diagram showing an example of an apparatus used to manufacture molybdenum trioxide particles, which are raw materials for molybdenum disulfide particles according to the present embodiment. Figure 2 is a diagram showing the X-ray diffraction (XRD) profiles of molybdenum disulfide particles obtained in Examples 1 to 3 superimposed. Figure 3 is a diagram showing the X-ray diffraction (XRD) profile of molybdenum disulfide particles obtained in Example 1. Figure 4 is a diagram showing the X-ray diffraction (XRD) profile of molybdenum disulfide particles obtained in Example 2. Figure 5 is a diagram showing the X-ray diffraction (XRD) profile of molybdenum disulfide particles obtained in Example 3. Figure 6 is a diagram showing the X-ray diffraction (XRD) profile of molybdenum disulfide particles obtained in Comparative Example 1. Figure 7 is a diagram showing the relationship between the firing temperature and the crystallite size in Examples 1 to 3. Figure 8 is a diagram showing the X-ray diffraction (XRD) profile used when calculating the degree of crystallinity of the molybdenum disulfide particles obtained in Example 2. Figure 9 is a diagram showing the X-ray diffraction (XRD) profile used when calculating the degree of crystallinity of the molybdenum disulfide particles obtained in Example 3. FIG. 10 is a diagram showing the relationship between the calcination temperature and the degree of crystallization in Examples 1 to 3. FIG. 11a is a diagram showing the relationship between the calcination temperature and the abundance ratio of 2H crystal structure and 3R crystal structure in the crystal phase in Examples 1 to 3. FIG. 11b is a diagram showing the relationship between the calcination temperature and the abundance ratio of the first and second crystal phases of the 2H crystal structure, the 3R crystal structure, and the amorphous phase in Examples 1 to 3 and Comparative Example 1. FIG. 12 is a graph showing the results of measuring the time dependence of the friction coefficient at 75°C in Example 4 and Comparative Example 3. Specific details for implementing the invention
[0033] Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings.
[0034] Molybdenum disulfide particles
[0035] The molybdenum disulfide particles of the present embodiment have a 2H crystal structure and a 3R crystal structure of molybdenum disulfide, and the abundance ratio of the 3R crystal structure in the crystalline phase of molybdenum disulfide is 10% or more, and the crystallite size of the 3R crystal structure calculated by extended Rietveld analysis based on the analytical formula L=Kλ / (βcosθ) using a profile obtained from powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source is 1 nm or more and 150 nm or less. In the above formula, K is an apparatus constant depending on the XRD optical system (incident side and detector side) and settings, L is the crystallite size [m], λ is the measured X-ray wavelength [m], K is a constant, β is the full width [rad], and θ is the Bragg angle of the diffraction line [rad].
[0036] The molybdenum disulfide (MoS2) particles of the present embodiment include a 2H crystal structure and a 3R crystal structure. Molybdenum disulfide, which is generally used as a lubricant, is a hexagonal solid lubricant and has a 2H crystal structure as its crystal structure (see FIG. 6). When molybdenum disulfide particles in which the abundance ratio of the 3R crystal structure in the crystalline phase of molybdenum disulfide is 10% or more are used as a lubricant, not only is it difficult to cause seizure even when a high load is applied, but it also has excellent friction characteristics that reduce the friction coefficient by 20-30%. The abundance ratio of the 3R crystal structure in the crystalline phase of molybdenum disulfide may be 5% or more and 60% or less, 20% or more and 60% or less, and preferably 20% or more and 60% or less, and may be 20% or more and 45% or less.
[0037] It can be confirmed that molybdenum disulfide particles have 2H crystal structures and 3R crystal structures by using, for example, extended Rietveld analysis software (Hyscore Plus, manufactured by Malvern Analytical) that can consider crystallite size. With this Rietveld analysis software, the entire XRD diffraction profile is simulated using a crystal structure model that includes crystallite size, and compared with the XRD diffraction profile obtained from an experiment. The crystal structure factors, such as crystal lattice constants and atomic coordinates of the crystal structure model, and weight fractions (abundance ratios) are optimized by the least squares method so that the residual between the experimentally obtained diffraction profile and the calculated diffraction profile is minimized. By identifying and quantifying each phase of the 2H crystal structure and 3R crystal structure with high precision, the crystallite size can be calculated in addition to the crystal structure type and its ratio calculated by conventional Rietveld analysis. Hereinafter, in this patent, the analysis method using the above-mentioned High Score Plus is referred to as "extended Rietveld analysis."
[0038] Media glasses D of molybdenum disulfide particles in this embodiment 50 It is preferable that the size be between 10 nm and 1000 nm.
[0039] Commercially available MoS2 is a crushed ore product containing a large amount of particles with a diameter exceeding 1 μm, and in lubricating compositions containing base oils with low viscosity and a small lubricant effect per weight, it becomes a factor in sedimentation. Meanwhile, as in the present embodiment, the above-mentioned media glasses D 50 Since this is 1000 nm or less, when molybdenum disulfide particles are used as a lubricant, it is difficult for seizure to occur even when a high load is applied. This is because, under high load conditions, when the friction surfaces of the contact materials come close to each other to a distance of less than 1 μm (i.e., 1000 nm), the lubricant is not expelled from this gap but remains there, making it possible to continuously maintain lubrication performance. Furthermore, the above-mentioned Media Glasses D 50Since this is 1000 nm or less, when used in a lubricating composition containing base oil, it is difficult to settle and has excellent storage stability.
[0040] In addition, the media glasses D of molybdenum disulfide particles 50 Since the particle size is 1000 nm or less, the molybdenum disulfide particles become floating components and are difficult to settle. Therefore, even if the friction surfaces of the contacting materials are arranged in a state where they are susceptible to gravity that is perpendicular or close to it, they can exist in a state of being inserted into the gap between the friction surfaces of the contacting materials at the time prior to contact. In addition, when the molybdenum disulfide enters the gap and receives the shear force characteristic of layered compounds, it causes slippage between crystal planes, which has the effect of lowering the coefficient of friction between the contact surfaces. Therefore, compared to conventional molybdenum disulfide particles that are prone to settling, it is believed that the cutting and wear of the contacting members at the start of contact can be prevented, and as a result, contribute to extending the lifespan of the friction surfaces of the contacting materials.
[0041] In addition, the molybdenum disulfide particles of the present embodiment can be supplied as a lubricant, for example, to the sliding parts of a plurality of metal spheres. In this case, when the metal spheres are pressed against each other until the distance between them becomes less than 1 μm (= 1000 nm) under high load, the above-mentioned media glasses D 50 Since this is small, less than 1000 nm, it is not excluded from the clearance between the metal spheres and can remain in the gap between them. Even in this situation, when subjected to a shear force characteristic of the layered compound, it causes slippage between the crystal planes to exhibit the effect of reducing the friction coefficient between the contact planes, and the probability of contact between the friction planes of the metal spheres (or contact area × time) remains low, so it is thought that it becomes difficult for the burning caused by rubbing to occur.
[0042] Media glasses D of the above molybdenum disulfide particles 50In terms of the above effect, 600 nm or less is preferable, 500 nm or less is more preferable, and 400 nm or less is even more preferable. The media glasses D of the molybdenum disulfide particles above 50 Silver, it may be 20nm or larger, or 40nm or larger. Media Glasses D of molybdenum disulfide particles 50 It is measured using, for example, a dynamic light scattering particle size distribution measuring device (Microtrack Bell, Nanotrac Wave II) or a laser diffraction particle size distribution measuring device (Shimadzu Seisakusho SALD-7000).
[0043] In addition, in the molybdenum disulfide particles of the present embodiment, the crystallite size of the 3R crystal structure is 1 nm or larger and 150 nm or smaller. If the crystallite size of the 3R crystal structure is 1 nm or larger and 150 nm or smaller, when used as a dispersant contained in a base oil such as a lubricating oil, slippage between layers becomes more likely to occur when subjected to shear force as the crystallite size becomes smaller when it enters the gap, thereby reducing the friction coefficient of the dispersion system and improving friction characteristics. It is preferable that the crystallite size of the 3R crystal structure is a value obtained by extended Rietveld analysis. The friction coefficient can be measured, for example, from a Strivec curve using a ball-on-disk tester or a four-hole tester.
[0044] The 3R crystal structure obtained by the above extended Rietveld analysis is preferably composed of a crystal phase having a crystallite size of 1 nm or more and 50 nm or less calculated based on the analysis formula in terms of the above effect, more preferably 5 nm or more and 50 nm or less, and more preferably 10 nm or more and 40 nm or less.
[0045] In addition, in the molybdenum disulfide particles of the present embodiment, it is preferable that the crystallite size of the 2H crystal structure is 1 nm or more and 150 nm or less. If the crystallite size of the 2H crystal structure is 1 nm or more and 150 nm or less, when used as a dispersant contained in a base oil such as a lubricating oil, the friction coefficient of the dispersion system can be reduced and friction characteristics can be improved.
[0046] It is preferable that the crystallite size of the above 2H crystal structure is a value obtained by extended Rietveld analysis. It is preferable that the above 2H crystal structure obtained by the above Rietveld analysis is a crystalline phase composed of crystallites having a crystallite size of 1 nm or more and 150 nm or less calculated based on the above analysis formula, and it is more preferable that the crystallite size is 5 nm or more and 150 nm or less.
[0047] The above 2H crystal structure obtained by extended Rietveld analysis preferably consists of a single crystalline phase composed of crystallites having a predetermined crystallite size. In the manufacturing method described below, a 2H crystal structure composed of a single crystalline phase can be obtained by setting the heating temperature during heat treatment to a relatively low temperature. In this case, the crystallite size of the above 2H crystal structure is more preferably 1 nm or larger and 20 nm or smaller, and more preferably 5 nm or larger and 15 nm or smaller.
[0048] The crystallite size of the 2H crystal structure and the crystallite size of the 3R crystal structure may be calculated, for example, using the peak full width at half maximum of the XRD diffraction profile.
[0049] Using the profile obtained from the above XRD, the abundance ratio (2H:3R) of the 2H crystal structure and the 3R crystal structure obtained by extended Rietveld analysis in the crystal phase is preferably 10:90 to 90:10. If the abundance ratio of the 3R crystal structure in the crystal phase is 10% or more and 90% or less, when molybdenum disulfide particles are used as a lubricant, it is difficult to cause seizure when a high load is applied, and the friction coefficient can be reduced by 20 to 30%.
[0050] Using the profile obtained from the above XRD, the abundance ratio (2H:3R) of the 2H crystal structure and the 3R crystal structure in the crystal phase obtained by extended Rietveld analysis is more preferably 10:90 to 80:20 and more preferably 40:60 to 80:20 in terms of the above effect.
[0051] In addition, the 2H crystal structure obtained by the extended Rietveld analysis described above may consist of a first crystal phase composed of crystallites having a predetermined crystallite size, and a second crystal phase having a crystallite size smaller than that of the first crystal phase. In the manufacturing method described below, a 2H crystal structure composed of the first crystal phase and the second crystal phase can be obtained by further heating the molybdenum disulfide particles as a post-treatment. The crystallite size of the first crystal phase of the 2H crystal structure may, for example, be greater than 20 nm and less than or equal to 150 nm, greater than or equal to 50 nm and less than or equal to 150 nm, or greater than or equal to 100 nm and less than or equal to 150 nm. However, for the reduction of the friction coefficient, it is preferable that the first crystal phase is not present in the crystal phase of the 2H crystal structure, or that its abundance ratio is low. In addition, the crystallite size of the second crystal phase of the above 2H crystal structure is preferably 1 nm or more and 20 nm or less, and may be 1 nm or more and 10 nm or less, or 5 nm or more and 15 nm or less.
[0052] The crystallite size of the first crystal phase of the 2H crystal structure, the crystallite size of the 3R crystal structure, and the crystallite size of the second crystal phase of the 2H crystal structure may also be calculated, for example, by using the peak half-width of the XRD diffraction profile, just as above.
[0053] It is preferable that the abundance ratio (2H (first crystal phase):3R:2H (second crystal phase)) of the first crystal phase of the 2H crystal structure, the 3R crystal structure, and the second crystal phase of the 2H crystal structure obtained by extended Rietveld analysis using the profile obtained from the above XRD be 30 to 0:10 to 70:80 to 15. If the abundance ratio of the first crystal phase of the 2H crystal structure, the 3R crystal structure, and the second crystal phase of the 2H crystal structure in the crystal phase is 30 to 10:10 to 70:80 to 15, when molybdenum disulfide particles are used as a lubricant, it is difficult to cause seizure when a high load is applied, and the friction coefficient can be reduced by 20 to 30%.
[0054] Using the profile obtained from the XRD above, the abundance ratio of the first crystal phase of the 2H crystal structure, the 3R crystal structure, and the second crystal phase of the 2H crystal structure obtained by extended Rietveld analysis is more preferably 30~0:10~70:80~15 in terms of the above effect, and more preferably 25~0:20~60:75~20.
[0055] In the profile obtained from powder X-ray diffraction (XRD) of the above molybdenum disulfide particles using Cu-Kα rays as an X-ray source, it is preferable that the peaks around 39.5° and 49.5° originate from the 2H crystal structure, the peaks around 32.5°, 39.5° and 49.5° originate from the 3R crystal structure, and the full width at half maximum of the peaks around 39.5° and 49.5° is 1° or more. Additionally, the above molybdenum disulfide particles may include crystal structures other than the 2H crystal structure and 3R crystal structure of molybdenum disulfide, such as a 1H crystal structure.
[0056] The fact that the molybdenum disulfide particles described above contain a metastable 3R crystal structure can be distinguished by the fact that, in the profile obtained from powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source, the peak at around 39.5° and the peak at around 49.5° are both composed of a composite peak of the 2H crystal structure and the 3R crystal structure.
[0057] In practice, the abundance of the 2H crystal structure is determined by using the profile obtained from the above powder X-ray diffraction (XRD) and the peak near 39.5° and the broad peak near 49.5°. Additionally, the abundance of the 3R crystal structure is determined by optimizing the difference between the peak near 39.5° and the broad peak near 49.5° into two peaks near 32.5° and two peaks near 39.5°. That is, either of the peak near 39.5° or the peak near 49.5° is a composite wave originating from the 2H crystal structure and the 3R crystal structure, and the abundance of the 2H crystal structure and the 3R crystal structure in molybdenum disulfide particles can be calculated using these composite waves.
[0058] In addition, molybdenum disulfide particles may contain an amorphous phase. The abundance of the amorphous phase of the molybdenum disulfide particles is expressed as 100 (%) - (degree of crystallinity (%)), and it is preferable that it be 5% or more, more preferable that it be 15% or more, and even more preferable that it be 20% or more. If the abundance of the amorphous phase of the molybdenum disulfide particles is 5% or more, the coefficient of friction is further reduced, and friction characteristics can be improved.
[0059] In the two-dimensional image taken with a transmission electron microscope (TEM), the shape of the primary particles of the molybdenum disulfide may be granular, spherical, plate-like, needle-like, string-like, ribbon-like, or sheet-like, and may include a combination of these shapes. The shape of the molybdenum sulfide is preferably disc-like, ribbon-like, or sheet-like, and the shape of 50 primary particles of molybdenum sulfide is preferably, on average, in the range of length (length) × width (horizontal) × thickness (height) = 50~1000nm × 50~1000nm × 3~100nm, more preferably in the range of 100~500nm × 100~500nm × 5~50nm, and particularly preferably in the range of 50~200nm × 50~200nm × 5~20nm. By being disc-shaped, ribbon-shaped, or sheet-shaped, the specific surface area of the molybdenum disulfide particles can be increased. Here, disc-shaped, ribbon-shaped, or sheet-shaped refers to a thin-layer shape. The aspect ratio of the primary particles of molybdenum sulfide, i.e., (length (horizontal and longitudinal dimensions)) / thickness (height)), is preferably 1.2 to 1200 as an average of 50 values, more preferably 2 to 800, more preferably 5 to 400, and particularly preferably 10 to 200.
[0060] Since the shape of the primary particles of the above molybdenum disulfide particles is not a simple sphere but a disc, ribbon, or sheet shape with a large aspect ratio, it is expected that the friction surfaces of the contacting materials can be covered more efficiently, and the probability of contact (or contact area × time) between the friction surfaces of the contacting materials can be reduced due to the occurrence of interphase slippage in the crystal structure, so it is thought that wear or seizure caused by rubbing becomes less likely to occur.
[0061] The specific surface area of the molybdenum disulfide particles measured by the BET method is preferably 10 m² / g or more, more preferably 30 m² / g or more, and particularly preferably 40 m² / g or more. The specific surface area of the molybdenum disulfide particles measured by the BET method may be 300 m² / g or less, or 200 m² / g or less.
[0062] The primary particles of the molybdenum disulfide particles can easily separate from each other by external forces such as friction, as the layers constituting the primary particles approach each other through relatively weak interactions. Therefore, when the primary particles of the molybdenum disulfide particles are placed between metals that are in contact with each other, the layers constituting the primary particles separate from each other due to the frictional force, thereby lowering the apparent coefficient of friction and also preventing contact between the metals that are in contact with each other.
[0063] If the specific surface area of the molybdenum disulfide particles measured by the BET method is 10 m² / g or more, it is believed that when the primary particles exist between metals that are in contact with each other, the contact area between the metals can be reduced, thereby contributing to both the improvement of lubricant performance and the prevention of seizure.
[0064] In the angular distribution function obtained from the broad-spectrum X-ray absorption microstructure (EXAFS) profile of the molybdenum K absorption group of the above molybdenum disulfide particles, the ratio (I / II) of the peak intensity I attributable to Mo-S and the peak intensity II attributable to Mo-Mo is preferably greater than 1.0, more preferably greater than 1.1, and particularly preferably greater than 1.2.
[0065] Whether the crystal structure of molybdenum disulfide is a 2H crystal structure or a 3R crystal structure, the distance between Mo and S is almost the same due to covalent bonding, so the intensity of the peak attributed to Mo-S in the broad-spectrum X-ray absorption fine structure (EXAFS) profile of the K absorption group of molybdenum is the same. On the other hand, since the 2H crystal structure of molybdenum disulfide is hexagonal, the same hexagon is located just below the 90˚ of the hexagon of the Mo atom, so the distance between Mo and Mo is reduced, and the peak intensity II attributed to Mo and Mo becomes stronger.
[0066] Conversely, since the 3R crystal structure of molybdenum disulfide is rhombohedral, the hexagon exists at a half-off angle rather than directly below 90˚ of the hexagon, so the distance between Mo-Mo increases, and the peak intensity II attributable to Mo-Mo is weakened.
[0067] In the pure 2H crystal structure of molybdenum disulfide, the above ratio (I / II) is reduced, but as it includes the 3R crystal structure, the above ratio (I / II) is increased.
[0068] In the 3R crystal structure, since the hexagons of each Mo atom in the three layers are offset from each other by half a hexagon, compared to the 2H crystal structure in which the hexagons of Mo atoms in the two layers are arranged vertically and regularly, it can be expected that the interaction between the layers is small and sliding becomes easier.
[0069] Even in the 2H crystal structure, if the crystallite size is small, it can be expected that slippage on the contact surface will occur more easily.
[0070] The conversion rate R of the above molybdenum trioxide particles to MoS2 C Since the presence of molybdenum trioxide is thought to have an adverse effect on lubrication performance, it is desirable that it be 70% or more, more desirable that it be 80% or more, and more desirable that it be 90% or more.
[0071] The above molybdenum disulfide particles have a conversion rate R to MoS2 C By showing a figure close to 100%, it can be said that the lubricating performance is achieved through heating by friction, but the lubricating characteristics are superior to other molybdenum disulfide materials or precursors that may contain molybdenum trioxide as a byproduct.
[0072] Conversion rate R of molybdenum trioxide particles to MoS2 C It can be obtained by the RIR (Reference Intensity Ratio) method from profile data obtained by X-ray diffraction (XRD) measurement of molybdenum disulfide particles. The RIR value K of molybdenum disulfide (MoS2). A and the integrated intensity I of the peak near 2θ = 14.4˚ ± 0.5˚ attributed to the (002) or (003) plane of molybdenum disulfide (MoS2). A , and, each molybdenum oxide (the raw material MoO3, and the reaction intermediate Mo9O 25 , Mo4O 11 RIR value K of ( , MoO2, etc.) B and each molybdenum oxide (the raw material MoO3, and the reaction intermediate Mo9O 25 , Mo4O 11 The integral strength I of the strongest sun peak (e.g., MoO2) B Using this, the conversion rate R to MoS2 from the following equation (1) C You can obtain.
[0073] R C (%)=( I A / KA ) / (Σ(I B / K B ))×100 … (1)
[0074] Here, the RIR values can be those listed in the Inorganic Crystal Structure Database (ICSD) (developed by the Chemical Information Association), and for the analysis, integrated powder X-ray analysis software (PDXL2, developed by Rigakusha) can be used.
[0075] In addition, the lubricating composition of the present embodiment preferably contains molybdenum disulfide particles (MoS2), but is not limited to this, and MoS x It may contain molybdenum sulfide particles represented by (X=1~3), and MoS x It may contain one or more types of molybdenum sulfide particles represented by (X=1~3).
[0076] Method for manufacturing molybdenum disulfide particles
[0077] The above molybdenum disulfide particles can be produced, for example, by heating molybdenum trioxide particles, in which the average particle size of the primary particles is 2 nm or more and 1000 nm or less, at a temperature of 200 to 1000°C in the presence of a sulfur source.
[0078] The average particle size of the primary particles of molybdenum trioxide refers to the average value of the primary particle sizes of 50 randomly selected primary particles when the molybdenum trioxide particles are photographed with a scanning electron microscope (SEM) or a transmission electron microscope (TEM), and the major axis (the Ferret diameter of the longest part observed) and the minor axis (the short Ferret diameter in the direction perpendicular to the Ferret diameter of the longest part) of the smallest unit particles (i.e., primary particles) constituting the aggregate in the two-dimensional image are measured and the average value is taken as the primary particle size.
[0079] In the above method for manufacturing molybdenum disulfide particles, it is preferable that the average particle size of the primary particles of the molybdenum trioxide particles be 1 μm or less. In terms of reactivity with sulfur, 600 nm or less is more preferable, 400 nm or less is more preferable, and 200 nm or less is particularly preferable. The average particle size of the primary particles of the molybdenum trioxide particles may be 2 nm or more, 5 nm or more, or 10 nm or more.
[0080] The molybdenum trioxide particles used in the manufacture of the above molybdenum disulfide particles preferably consist of an aggregate of primary particles containing a β crystal structure of molybdenum trioxide. Compared to conventional molybdenum trioxide particles consisting solely of α crystals as a crystal structure, the above molybdenum trioxide particles exhibit good reactivity with sulfur and, since they contain a β crystal structure of molybdenum trioxide, the conversion rate R to MoS2 in the reaction with a sulfur source C It can be made larger.
[0081] The β crystal structure of molybdenum trioxide can be confirmed by the presence of a peak (2θ: near 23.01˚, No. 86426 (Inorganic Crystal Structure Database (ICSD))) attributed to the (011) plane of the β crystal of MoO3 in the profile obtained from powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source. The α crystal structure of molybdenum trioxide can be confirmed by the presence of a peak (2θ: near 27.32˚, No. 166363 (Inorganic Crystal Structure Database (ICSD))) in the (021) plane of the α crystal of MoO3.
[0082] In the above molybdenum trioxide particles, in the profile obtained from powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source, it is preferable that the ratio (β(011) / α(021)) of the peak intensity attributable to the (011) plane of the β crystal of MoO3 to the peak intensity attributable to the (021) plane of the α crystal of MoO3 (2θ: near 27.32˚_No. 166363 (Inorganic Crystal Structure Database (ICSD))) is 0.1 or greater.
[0083] The peak intensity attributable to the (011) plane of the β crystal of MoO3 and the peak intensity attributable to the (021) plane of the α crystal of MoO3 are each calculated by reading the maximum intensity of the peaks to obtain the ratio (β(011) / α(021)).
[0084] In the molybdenum trioxide particles above, the ratio (β(011) / α(021)) is preferably 0.1 to 10.0, more preferably 0.2 to 10.0, and particularly preferably 0.4 to 10.0.
[0085] The β crystal structure of molybdenum trioxide has a wavenumber of 773,848 cm⁻¹ in the Raman spectrum obtained from Raman spectroscopic measurements. -1 and 905cm -1 It can also be confirmed by the presence of a peak at . The α-crystal structure of molybdenum trioxide is at wavenumbers 663 and 816 cm⁻¹. -1 and 991cm -1 It can be confirmed by the presence of a peak at.
[0086] The average particle size of the primary particles of the above molybdenum trioxide powder may be 5 nm or more and 2000 nm or less.
[0087] Examples of sulfur sources include sulfur and hydrogen sulfide, and these may be used alone or in combination of two.
[0088] The above method for manufacturing molybdenum disulfide particles may include heating molybdenum trioxide particles, which are composed of an aggregate of primary particles including a β crystal structure of molybdenum trioxide, at a temperature of 100 to 800°C in the absence of a sulfur source, and then heating at a temperature of 200 to 1000°C in the presence of a sulfur source.
[0089] The heating time in the presence of sulfur is preferably a time during which the sulfidation reaction proceeds sufficiently, and may be 1 to 20 hours, 2 to 15 hours, or 3 to 10 hours.
[0090] In the above method for manufacturing molybdenum disulfide particles, the input ratio of the sulfur source's S amount to the MoO3 amount of the molybdenum trioxide particles is preferably such that the sulfidation reaction proceeds sufficiently. For 100 mol% of the MoO3 amount of the molybdenum trioxide particles, it is preferable that the sulfur source's S amount be 450 mol% or more, more preferable that it be 600 mol% or more, and even more preferable that it be 700 mol% or more. For 100 mol% of the MoO3 amount of the molybdenum trioxide particles, the sulfur source's S amount may be 3000 mol% or less, 2000 mol% or less, or 1500 mol% or less.
[0091] In the above method for manufacturing molybdenum disulfide particles, the heating temperature in the presence of the sulfur source is preferably a temperature at which the sulfidation reaction proceeds sufficiently, preferably 320°C or higher, more preferably 340°C or higher, and more preferably 360°C or higher. Additionally, the heating temperature may be 320 to 1000°C, 340 to 1000°C, or 360 to 500°C. By making the heating temperature low, the degree of crystallinity of the molybdenum disulfide particles is reduced, and the proportion of the amorphous phase can be increased.
[0092] In the above method for manufacturing molybdenum disulfide particles, as a post-treatment, the obtained molybdenum disulfide particles may be cooled and then heated as necessary. In this heat treatment, it is preferable to calcin the molybdenum disulfide particles, for example, under an inert atmosphere. By heating and calcining the obtained molybdenum disulfide particles, crystallization of the amorphous phase is promoted, and the degree of crystallization is improved. In addition, along with the improvement in the degree of crystallization, new 2H crystal structures and 3R crystal structures are formed, respectively, and the abundance ratio of the 2H crystal structure and the 3R crystal structure changes. When reheating is performed as a post-treatment in this way, the degree of crystallization of the molybdenum disulfide particles increases, and the tendency for each layer to peel off due to lubrication is reduced to some extent; however, since the abundance ratio of the 3R crystal structure, which contributes to the improvement of friction characteristics, increases, the friction characteristics can be improved compared to the case of only the 2H crystal structure. In addition, by changing the temperature when heating the obtained molybdenum disulfide particles, the abundance ratio of the 2H crystal structure and the 3R crystal structure can be adjusted.
[0093] When the obtained molybdenum disulfide particles are heated and calcined at a temperature above a predetermined temperature, causing the amorphous phase to change into a 2H crystal structure, a second crystal phase is newly created, consisting of crystallites with a crystallite size of 20 nm or less, preferably 10 nm or less. At this time, in the 2H crystal structure, if there were crystallites with a crystallite size of 10 nm or less before heating the molybdenum disulfide particles, after heating the molybdenum disulfide particles, said crystallites grow to a crystallite size of 100 nm or more, and a first crystal phase is created, consisting of said grown crystallites.
[0094] As described above, among the crystal structures of molybdenum disulfide particles, it is inferred that the crystalline phase constituting the 3R crystal structure contributes to the improvement of frictional properties, while the first crystalline phase constituting the 2H crystal structure does not contribute to frictional properties or may be a factor that degrades frictional properties. Therefore, from the perspective of increasing the abundance of the 3R crystal structure phase while keeping the abundance of the first crystalline phase of the 2H crystal structure as low as possible, the heating temperature of the molybdenum disulfide particles during post-treatment is preferably 500 to 900°C, and more preferably 500 to 800°C.
[0095] In addition, the heating rate of molybdenum disulfide particles in post-treatment is preferably 1℃ / min or more and 50℃ / min or less, and more preferably 2℃ / min or more and 10℃ / min or less.
[0096] In the above method for manufacturing molybdenum disulfide particles, it is preferable that the molybdenum trioxide particles have a MoO3 content of 99.5% or higher as measured by X-ray fluorescence (XRF). By this, the conversion rate R to MoS2 C It is possible to obtain molybdenum disulfide with good storage stability and high purity, without the risk of generating disulfides of impurity origin.
[0097] It is preferable that the above molybdenum trioxide particles have a specific surface area of 10 m² / g to 100 m² / g as measured by the BET method.
[0098] In the above molybdenum trioxide particles, the specific surface area is preferably 10 m² / g or more, more preferably 20 m² / g or more, and more preferably 30 m² / g or more, in terms of improving reactivity with sulfur. In the above molybdenum trioxide particles, it is preferably 100 m² / g or less in terms of facilitating manufacturing, and it may be 90 m² / g or less, or 80 m² / g or less.
[0099] For the molybdenum trioxide particles above, it is preferable that the ratio (I / II) of the peak intensity I attributable to Mo-O and the peak intensity II attributable to Mo-Mo in the broad-spectrum X-ray absorption microstructure (EXAFS) profile of the K absorption group of molybdenum is greater than 1.1.
[0100] The peak intensity I attributable to Mo-O and the peak intensity II attributable to Mo-Mo are each read to determine the ratio (I / II). The ratio (I / II) is considered to serve as a standard for obtaining the β crystal structure of MoO3 in molybdenum trioxide particles, and the larger the ratio (I / II), the better the reactivity with sulfur.
[0101] In the above molybdenum trioxide particles, the ratio (I / II) is preferably 1.1 to 5.0, may be 1.2 to 4.0, or may be 1.2 to 3.0.
[0102] (Method for manufacturing molybdenum trioxide particles)
[0103] The above molybdenum trioxide particles can be manufactured by vaporizing a molybdenum oxide precursor compound to form molybdenum trioxide vapor, and cooling the molybdenum trioxide vapor.
[0104] The above method for manufacturing molybdenum trioxide particles comprises calcining a raw material mixture comprising a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound, and vaporizing the molybdenum oxide precursor compound to form molybdenum trioxide vapor, wherein the ratio of the metal compound to 100 mass% of the raw material mixture is preferably 70 mass% or less in terms of oxide.
[0105] The above method for manufacturing molybdenum trioxide particles can be appropriately carried out using the manufacturing apparatus (1) shown in FIG. 1.
[0106] FIG. 1 is a schematic diagram showing an example of an apparatus used to manufacture molybdenum trioxide particles, which are raw materials for molybdenum disulfide particles according to the present embodiment.
[0107] As shown in FIG. 1, the manufacturing apparatus (1) has a calcination furnace (2) that calcines a molybdenum trioxide precursor compound or a mixture of raw materials and vaporizes the molybdenum trioxide precursor compound, a cross-shaped cooling pipe (3) connected to the calcination furnace (2) and atomizes the molybdenum trioxide vapor vaporized by calcination, and a recovery device (4) which is a recovery means for recovering the molybdenum trioxide particles atomized by the cooling pipe (3). At this time, the calcination furnace (2) and the cooling pipe (3) are connected via an exhaust port (5). In addition, the cooling pipe (3) has an external air intake port (not shown) with an opening adjustment damper (6) at the left end and an observation window (7) at the top end. A first air blower device (8) is connected to the recovery device (4). By blowing air through the blower device (8), the internal gas of the recovery unit (4) and the cooling pipe (3) is sucked in, and outside air is blown into the cooling pipe (3) from the opening adjustment damper (6) of the cooling pipe (3). That is, by the blower device (8) exhibiting a suction function, air is blown into the cooling pipe (3) passively. In addition, the manufacturing device (1) may have an external cooling device (9), and thereby it becomes possible to arbitrarily control the cooling conditions of the molybdenum trioxide vapor generated in the kiln (2).
[0108] By opening the opening adjustment damper (6), air is introduced from the outside air intake, and the molybdenum trioxide vapor vaporized in the kiln (2) is cooled under an air atmosphere and formed into molybdenum trioxide particles, thereby making the ratio (I / II) greater than 1.1, and the β crystal structure of MoO3 in the molybdenum trioxide particles is easily obtained. Cooling the molybdenum trioxide vapor under a low oxygen concentration under a nitrogen atmosphere, such as when the molybdenum trioxide vapor is cooled using liquid nitrogen, increases the oxygen defect density, making it easy to lower the ratio (I / II).
[0109] The above molybdenum oxide precursor compound is not particularly limited as long as it forms molybdenum trioxide vapor upon calcination, but includes metallic molybdenum, molybdenum trioxide, molybdenum dioxide, molybdenum sulfide, ammonium molybdate, and phosphomolybdic acid (H3PMo 12 O 40 ), silomolybdic acid (H4SiMo 12 O 40 ), aluminum molybdate, silicon molybdate, magnesium molybdate (MgMo n O 3n+1 (n=1~3)), sodium molybdate (Na2Mo n O 3n+1 (n=1~3)), titanium molybdate, iron molybdate, potassium molybdate (K2Mo n O 3n+1 (n=1~3)), zinc molybdate, boron molybdate, lithium molybdate (Li2Mo n O 3n+1Examples include (n=1~3)), cobalt molybdate, nickel molybdate, manganese molybdate, chromium molybdate, cesium molybdate, barium molybdate, strontium molybdate, yttrium molybdate, zirconium molybdate, copper molybdate, etc. These molybdenum oxide precursor compounds may be used alone or in combination of two or more types. The form of the molybdenum oxide precursor compound is not particularly limited and, for example, may be in a powder form such as molybdenum trioxide or in a liquid form such as an aqueous solution of ammonium molybdate, but preferably, it is in a powder form that has good handling properties and energy efficiency.
[0110] It is particularly preferable to use commercially available α-crystalline molybdenum trioxide as the molybdenum trioxide precursor compound. In addition, when ammonium molybdate is used as the molybdenum oxide precursor compound, the vaporized molybdenum oxide precursor compound becomes the molybdenum trioxide, as it is converted into thermodynamically stable molybdenum trioxide by calcination.
[0111] Molybdenum trioxide vapor can also be formed by calcining a raw material mixture comprising a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound.
[0112] Among these, it is preferable that the molybdenum oxide precursor compound contains molybdenum trioxide, in terms of ease of controlling the purity of the obtained molybdenum trioxide powder, the average particle size of the primary particles, and the crystal structure.
[0113] There are cases where a molybdenum oxide precursor compound and a metal compound other than the said molybdenum oxide precursor compound form an intermediate, but even in this case, the intermediate decomposes through calcination, and molybdenum trioxide can be vaporized into a thermodynamically stable form.
[0114] Among the metal compounds other than the molybdenum oxide precursor compound, it is preferable to use an aluminum compound to prevent scratching of the kiln, and it is not necessary to use a metal compound other than the molybdenum oxide precursor compound to improve the purity of the molybdenum trioxide particles.
[0115] The metal compound other than the molybdenum oxide precursor compound is not particularly limited and may include, for example, an aluminum compound, a silicon compound, a titanium compound, a magnesium compound, a sodium compound, a potassium compound, a zirconium compound, a yttrium compound, a zinc compound, a copper compound, an iron compound, etc. Among these, it is preferable to use the aluminum compound, the silicon compound, the titanium compound, or the magnesium compound as the metal compound.
[0116] There are cases where a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound form an intermediate, but even in this case, the intermediate can be decomposed by calcination to vaporize molybdenum trioxide into a thermodynamically stable form.
[0117] As a metal compound other than the molybdenum oxide precursor compound, it is preferable to use an aluminum compound to prevent scratching of the kiln. In the above manufacturing method, in order to improve the purity of the molybdenum trioxide powder, it is not necessary to use a metal compound other than the molybdenum oxide precursor compound.
[0118] Examples of aluminum compounds include aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition aluminum oxides (γ-aluminum oxide, δ-aluminum oxide, θ-aluminum oxide, etc.), α-aluminum oxide, and mixed aluminum oxides having two or more crystal phases.
[0119] When calcining a raw material mixture comprising a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound, the content ratio of the molybdenum oxide precursor compound relative to 100 mass% of the raw material mixture is preferably 40 mass% or more and 100 mass% or less, and may be 45 mass% or more and 100 mass% or less, or 50 mass% or more and 100 mass% or less.
[0120] As for the calcination temperature, it varies depending on the molybdenum oxide precursor compound, metal compound, and desired molybdenum trioxide particles used, but generally, it is desirable to set it to a temperature at which the intermediate can decompose. For example, when a molybdenum compound is used as the molybdenum oxide precursor compound and an aluminum compound is used as the metal compound, the calcination temperature is preferably 500 to 1500°C, more preferably 600 to 1550°C, and even more preferably 700 to 1600°C, in order to form aluminum molybdate as an intermediate.
[0121] Regarding the firing time, there are no particular limitations, but for example, it can be 1 minute to 30 hours, 10 minutes to 25 hours, or 100 minutes to 20 hours.
[0122] The heating rate varies depending on the molybdenum oxide precursor compound used, the metal compound, and the desired molybdenum trioxide particles, but from the perspective of manufacturing efficiency, it is preferable to be 0.1°C / min to 100°C / min, more preferable to be 1°C / min to 50°C / min, and even more preferable to be 2°C / min to 10°C / min.
[0123] The internal pressure within the kiln is not particularly limited and may be either positive or reduced pressure; however, from the perspective of effectively discharging the molybdenum oxide precursor compound from the kiln to the cooling piping, it is preferable to perform the calcination under reduced pressure. Specifically, the degree of reduced pressure is preferably -5000 Pa to -10 Pa, more preferably -2000 Pa to -20 Pa, and even more preferably -1000 Pa to -50 Pa. A reduced pressure of -5000 Pa or higher is desirable in that the high airtightness or mechanical strength of the kiln is not excessively required, and manufacturing costs can be reduced. On the other hand, a reduced pressure of -10 Pa or lower is desirable in that it prevents clogging of the molybdenum oxide precursor compound at the discharge port of the kiln.
[0124] In addition, when blowing gas into the kiln during firing, the temperature of the blown gas is preferably 5 to 500°C, and more preferably 10 to 100°C.
[0125] In addition, for an effective volume of 100L of the kiln, it is preferable that the airflow velocity of the gas be 1L / min or more and 500L / min or less, and more preferable that it be 10L / min or more and 200L / min or less.
[0126] The temperature of the vaporized molybdenum trioxide vapor varies depending on the type of molybdenum oxide precursor compound used, but it is preferably 200 to 2000°C, and more preferably 400 to 1500°C. Also, if the temperature of the vaporized molybdenum trioxide vapor is 2000°C or lower, it tends to be easily atomized by blowing outside air (0 to 100°C) in the cooling piping.
[0127] The discharge rate of molybdenum trioxide vapor discharged from the kiln can be controlled by the amount of the molybdenum oxide precursor compound used, the amount of the metal compound, the temperature of the kiln, the blowing of gas into the kiln, and the diameter of the kiln exhaust port. Although it varies depending on the cooling capacity of the cooling pipe, the discharge rate of molybdenum trioxide vapor from the kiln to the cooling pipe is preferably 0.001 g / min or more and 100 g / min or less, and more preferably 0.1 g / min or more and 50 g / min or less.
[0128] In addition, the content of molybdenum trioxide vapor contained in the gas discharged from the kiln is preferably 0.01 mg / L or more and 1000 mg / L or less, and more preferably 1 mg / L or more and 500 mg / L or less.
[0129] Next, the above molybdenum trioxide vapor is cooled and granulated.
[0130] Cooling of molybdenum trioxide vapor is carried out by lowering the temperature of the cooling pipe. At this time, cooling means may include cooling by blowing gas into the cooling pipe as described above, cooling by a cooling mechanism in the cooling pipe, and cooling by an external cooling device.
[0131] It is preferable to perform the cooling of molybdenum trioxide vapor under an air atmosphere. By cooling the molybdenum trioxide vapor under an air atmosphere and forming it into molybdenum trioxide particles, the ratio (I / II) can be made greater than 1.1, and the β crystal structure of MoO3 is easily obtained in the molybdenum trioxide particles.
[0132] The cooling temperature (temperature of the cooling pipes) is not particularly limited, but is preferably -100 to 600°C, and more preferably -50 to 400°C.
[0133] The cooling rate of molybdenum trioxide vapor is not particularly limited, but is preferably 100°C / s or more and 100,000°C / s or less, and more preferably 1,000°C / s or more and 50,000°C / s or less. In addition, as the cooling rate of molybdenum trioxide vapor increases, molybdenum trioxide particles with a small particle size and a large specific surface area tend to be obtained.
[0134] When the cooling means is cooling by blowing gas into a cooling pipe, the temperature of the blown gas is preferably -100 to 300°C, and more preferably -50 to 100°C.
[0135] In addition, the airflow velocity of the gas is preferably 0.1 m³ / min or more and 20 m³ / min or less, and more preferably 1 m³ / min or more and 10 m³ / min or less. If the airflow velocity of the gas is 0.1 m³ / min or more, it is desirable in that a high cooling rate can be achieved and blockage of the cooling pipes can be prevented. On the other hand, if the airflow velocity of the gas is 20 m³ / min or less, it is desirable in that an expensive first airflow means (such as a blower) becomes unnecessary and manufacturing costs can be lowered.
[0136] The particles obtained by cooling molybdenum trioxide vapor are transported to a recovery unit and recovered.
[0137] The above method for manufacturing molybdenum trioxide particles may involve cooling the molybdenum trioxide vapor to obtain the particles, and then calcining them again at a temperature of 100 to 320°C.
[0138] That is, the molybdenum trioxide particles obtained by the above method for manufacturing molybdenum trioxide particles may be calcined again at a temperature of 100 to 320°C. The calcination temperature for the subsequent calcination may be 120 to 280°C or 140 to 240°C. The calcination time for the subsequent calcination may be, for example, 1 minute to 4 hours, 10 minutes to 5 hours, or 100 minutes to 6 hours. However, by calcining again, some of the β crystal structure of molybdenum trioxide is lost, and if calcined at a temperature of 350°C or higher for 4 hours, the β crystal structure in the molybdenum trioxide particles is lost, and the above ratio (β(011) / α(021)) becomes 0, and the reactivity with sulfur is impaired.
[0139] By the method for manufacturing molybdenum trioxide particles described above, molybdenum trioxide particles suitable for manufacturing molybdenum disulfide particles can be manufactured.
[0140] Lubricating composition
[0141] The lubricating composition of the present embodiment contains the molybdenum disulfide particles and a base oil composed of one or more types of mineral oil, synthetic oil, and partially synthetic oil.
[0142] Mineral oil base oils include oils obtained by rock drilling, oils obtained from plants or animals, and mixtures thereof. Examples of such oils include, but are not limited to, castor oil, lard oil, olive oil, peanut oil, corn oil, soybean oil, linseed oil, liquid petroleum, and paraffinic, naphthenic, or paraffin-naphthenic mixed base oils. Such base oils may be partially or completely hydrogenated if desired.
[0143] Examples of synthetic base oils include polyalphaolefin-based, hydrocarbon-based, ester-based, ether-based, silicone-based, alkylnaphthalene-based, or perfluoroalkyl polyether-based base oils.
[0144] A partially synthetic base oil refers to a base oil that is a mixture of these mineral oils and synthetic oils.
[0145] As the base oil for the above lubricating composition, any base oil generally used in lubricating compositions may be used without limitation.
[0146] The kinematic viscosity at 40°C of the base oil used in the lubricating composition of the present embodiment may be 1 mm² / s or more and 1000 mm² / s or less, 5 mm² / s or more and 200 mm² / s or less, or 10 mm² / s or more and 150 mm² / s or less. In the lubricating composition of the present embodiment, the median eyeglass D obtained by the dynamic light scattering method of molybdenum disulfide particles 50 Since the particle size is small, ranging from 10 nm to 1000 nm, the sedimentation of molybdenum disulfide particles can be suppressed even when using a base oil with relatively low viscosity.
[0147] The above lubricating composition preferably contains molybdenum disulfide particles, which are the lubricant, in an amount of 0.0001 mass% or more and 10 mass% or less based on 100 mass% of the total mass of the above lubricating composition, more preferably contains 0.01 mass% or more and 10 mass% or less, and even more preferably contains 0.01 mass% or more and 1 mass% or less.
[0148] The lubricating composition according to the present embodiment may further contain organometallic complex particles in the lubricating composition. It is preferable that the lubricating composition contains 0.0001 mass% or more and 10 mass% or less of organometallic complex particles with respect to 100 mass% of the total mass of the lubricating composition containing the lubricating composition and organometallic complex particles, more preferable that it contains 0.01 mass% or more and 10 mass% or less, and more preferable that it contains 0.01 mass% or more and 1 mass% or less. By containing 0.0001 mass% or more and 10 mass% or less of organometallic complex particles, the coefficient of friction can be significantly reduced, and it is also possible to maintain a low coefficient of friction over a long period of time.
[0149] Representative materials as organometallic complexes constituting organometallic complex particles include organomolybdenum complexes such as molybdenum dialkyldithiocarbamate (MoDTC) and molybdenum dialkyldithiophosphate (MoDTP). Additionally, organozinc complexes such as zinc dialkyldithiophosphate (ZnDTP) may be contained. Furthermore, multiple types of these known organometallic complex particles may be combined and contained.
[0150] The pre-electric lubricating composition and, furthermore, the lubricating composition may contain known additives such as detergents, viscosity modifiers, anti-foaming agents, corrosion inhibitors, rust inhibitors, antioxidants, anti-wear agents, and friction modifiers.
[0151] The above lubricating composition may additionally contain a known dispersant contained in general lubricating oil. By further suppressing sedimentation through the presence of the dispersant, storage stability can be reliably ensured.
[0152] [Example]
[0153] The embodiments of the present invention are described below. The present invention is not limited to the following embodiments.
[0154] [Synthetic Example]
[0155] (Preparation of molybdenum trioxide particles)
[0156] A kiln equivalent to a heat-resistant vessel, a cooling pipe equipped with an external air supply port, and a dust collector for recovering molybdenum oxide were prepared. The production of metal oxides was carried out using an RHK simulator (manufactured by Noritake Company Limited, Inc.) as the kiln and a VF-5N dust collector (manufactured by Amanosha) as the dust collector.
[0157] 1.5 kg of aluminum hydroxide (manufactured by Nihon Keiki Kinzoku Co., Ltd.) and 1 kg of molybdenum trioxide (manufactured by Nihon Muki Co., Ltd.) were mixed and then placed into a sheath. The kiln, cooling pipes, and dust collector were connected, and the mixture was calcined at a temperature of 1100°C for 10 hours. During calcination, outside air (air flow rate: 150 L / min, outside air temperature: 25°C) was introduced from the side and bottom of the kiln. Since molybdenum trioxide evaporates inside the kiln and then cools near the dust collector to precipitate as particles, the molybdenum trioxide was recovered by the dust collector.
[0158] After firing, 1.0 kg of blue aluminum oxide powder and 0.8 kg of molybdenum trioxide recovered by a dust collector were removed from the sheath.
[0159] The recovered molybdenum trioxide had a primary particle size of 1 μm or less, and by fluorescence X-ray measurement, it was confirmed that the purity of the molybdenum trioxide was 99.8%.
[0160] (Manufacture of molybdenum disulfide particles)
[0161] [Example 1]
[0162] 40.0 g (277.9 mmol) of molybdenum trioxide prepared in Synthesis Example 1 and 40.0 g (1250 mmol, 4.5 equivalents relative to Mo atoms) of sulfur powder (manufactured by Kanto Chemical Co., Ltd.) were added to an alumina crucible and mixed with a stirring rod to ensure the powders were homogeneous. After mixing, a lid was placed on the alumina crucible, and the mixture was placed in a high-temperature atmosphere calcination furnace (manufactured by Motoyama Co., Ltd., SKM-2030P-OP). The inside of the furnace was vacuumed and then purged with nitrogen before calcination was performed. The calcination conditions were as follows: the temperature was raised at a rate of 5°C / min from a room temperature of 25°C, and after reaching 500°C, it was maintained for 4 hours. During the calcination process, nitrogen gas was blown at a rate of 0.5 L / min. Afterward, the inside of the furnace was cooled by natural air cooling to obtain 44.5 g of molybdenum disulfide particles.
[0163] For this sample of molybdenum disulfide particles, the surface area was measured using a specific surface area meter (Microtrackbell, BELSORP-mini), and the surface area per 1g of sample measured from the amount of nitrogen gas adsorbed by the BET method was calculated as the specific surface area and was 44.5㎡ / g.
[0164] [Example 2]
[0165] Molybdenum disulfide particles were prepared in the same manner as in Example 1, and then 3.39 g of the molybdenum disulfide particles were placed in an alumina crucible (manufactured by Tokyo Glass Kikai Co., Ltd., BA-0), covered with a lid, and the molybdenum disulfide particles were calcined in a tubular furnace (manufactured by Yamada Electric Co., Ltd., TSS-1130-P) under a nitrogen atmosphere at a heating rate of 5℃ / min and a calcination temperature of 950℃ for 4 hours, and then naturally cooled to obtain 3.27 g of molybdenum disulfide particles.
[0166] [Example 3]
[0167] Except for changing the calcination temperature of the molybdenum disulfide particles to 1100 degrees, 3.13 g of molybdenum disulfide particles were obtained with an input amount of 3.41 g in the same manner as in Example 2.
[0168] [Comparative Example 1]
[0169] Commercially available molybdenum disulfide (MoS2) particles (manufactured by Kanto Kagakusha, molybdenum disulfide reagent) were prepared.
[0170] The molybdenum disulfide particles obtained in Examples 1 to 3 and Comparative Example 1 were measured and evaluated by the following method.
[0171] [Identification and Interpretation of Crystal Structure]
[0172] A sample of molybdenum disulfide particles was filled smoothly onto a measuring surface in a SUS measuring sample holder with a thickness of 2.4 mm and an inner diameter of 27 mm, and the sample was set in a multi-purpose X-ray diffraction (XRD) device (Malvern Medical, Empyrean 3). Using Cu / Kα rays, 45 kV / 40 mA, a monochromator on the incident side and a semiconductor high-speed detector (1D mode) on the detector side, and a rotary stage by the focusing method, measurements were performed under conditions of a measurement time of 8 minutes (Examples 1 and 2, Comparative Example 1) or 10 minutes (Example 3), a step size of 0.066 degrees (Examples 1 and 2, Comparative Example 1) or 0.026 degrees (Example 3), and a scanning range of 5 degrees or more and 100 degrees or less, and an XRD profile was obtained.
[0173] Rietveld analysis including determinant size evaluation was performed using software (Malbern Medical Laboratory, HighScore Plus).
[0174] The degree of crystallization of molybdenum disulfide particles was calculated by (1) determining the boundary line between the device-derived background A and the obtained diffraction profile in the range of 10 to 95° and subtracting background A from the obtained diffraction profile, (2) determining the broad peak B, called the amorphous halo, derived from the amorphous phase in the range of 10 to 95° and further subtracting background B from the obtained diffraction profile, and (3) dividing the sum of the peak intensities derived from the crystal above background A and amorphous halo B by the sum of the intensities in the XRD profile after subtracting background A. The maximum value of the degree of crystallization is 99.95%, indicating a state in which all molybdenum disulfide particles are crystallized.
[0175] The abundance ratio of the first crystal phase of the 2H crystal structure, the 3R crystal structure, and the second crystal phase of the 2H crystal structure in the molybdenum disulfide particles was specifically determined in Example 1 by determining the crystallite size and abundance ratio of the 2H crystal structure using broad peaks around 40° and 50°, and by optimizing the 3R crystal structure parameters using the difference between two peaks around 33° and two peaks around 40°, thereby reproducing the entire measured XRD profile.
[0176] In Examples 2 and 3, where the XRD profile could not be sufficiently fitted even with the above, a crystal structure having a crystallite size smaller than the 2H crystal structure (crystal phase) in the crystal phase was set, and the entire measured XRD profile was reproduced.
[0177] [Basic formulas and calculations for evaluating determinant size]
[0178] Generally, diffraction profiles were used, and the crystallite sizes of the 2H crystal structure (first crystal phase and second crystal phase) and 3R crystal structure were determined using the analytical formula L=Kλ / βcosθ as the basis. In the above formula, K is an instrument constant that depends on the XRD optical system (incident side and detector side) and settings, L is the crystallite size [m], λ is the measured X-ray wavelength [m], β is the full width [rad], and θ is the Bragg angle of the diffraction line [rad].
[0179] [Molybdenum disulfide particles' media glasses D 50 Measurement of]
[0180] 0.1 g of molybdenum disulfide powder was added to 20 cc of acetone and subjected to ultrasonic treatment in an ice bath for 4 hours. Subsequently, a measurement sample was obtained by further adjusting the concentration with acetone to the measurable range of a dynamic light scattering particle size distribution analyzer (manufactured by Microtrack Bell, Nanotrac Wave II). Using this measurement sample, the particle size distribution in the range of 0.0001 µm to 10 µm was measured using the dynamic light scattering particle size distribution analyzer, and Media Glasses D 50(z-mean) was calculated. Also, Media Glasses D 50 For the case exceeding 10㎛ (Comparative Example 1), a solution was prepared in the same manner, and the particle size distribution in the range of 0.015㎛ to 500㎛ was measured using a laser diffraction particle size distribution measuring device (Shimadzu Seisakusho, SALD-7000), and Media Glasses D 50 It produced.
[0181] [Measurement of (I / II) of molybdenum disulfide particles]
[0182] 36.45 mg of molybdenum disulfide particles and 333.0 mg of boron nitride were mixed in a mortar and pestle. 123.15 mg of this mixture was weighed and compression-molded into a φ8 mm tablet to obtain a measurement sample. Using this measurement sample, the broad-spectrum X-ray absorption fine structure (EXAFS) was measured by transmission using BL5S1 at the Aichi Synchrotron Optical Center. For the analysis, Athena (Internet<URL:https: / / bruceravel.github.io / demeter / > used ).
[0183] In the angular distribution function obtained from this profile, the ratio (I / II) of the peak intensity I attributable to Mo-S and the peak intensity II attributable to Mo-Mo was 1.26 (=19 / 15).
[0184] [Measurement of Friction Coefficient and Friction Evaluation of Lubricating Composition Containing Molybdenum Disulfide Particles]
[0185] A lubricating composition was prepared by adding 10 parts by mass of an additive (Sanyo Gassei Co., Ltd., Acroube 702) and 0.08 parts by mass of the molybdenum disulfide particles to 90 parts by mass of lubricating oil (JXTG, Super Oil N32) and ultrasonically dispersing for 1 hour.
[0186] A friction and wear test was performed on a rheometer (manufactured by Anton Passa, MCR-502) equipped with a temperature-controlled dedicated stage (tribocell) for evaluating sliding characteristics. The flat portions of three SUJ2 special stainless steel cylindrical pins were tilted 45 degrees in the height direction, and the contact surfaces were immersed in a stage arranged at 120 degrees horizontally from each other when viewed from directly above, by placing the lubricating composition prepared by the above method into the stage. A 1 / 2-inch SUJ2 special stainless steel sphere was then brought into contact with the pins, and a specified load was applied in the vertical direction. After standing for 5 minutes, the rotational speed of the SUJ2 sphere was varied from 3.0 × 10⁻⁵ rpm to 3120 rpm, and the friction coefficient at each rotational speed was obtained. If the friction coefficient was less than or equal to the friction coefficient of the comparative example, it was marked as "Good" (○); if it was "Best" (◎); and if it exceeded or was equal to the friction coefficient of the comparative example, it was marked as "Poor" (×).
[0187] The results of the above measurements and evaluations are shown in Tables 1 and 2 and Figures 2 to 11b.
[0188] [Table 1]
[0189]
[0190] [Table 2]
[0191]
[0192] First, a portion of the X-ray diffraction (XRD) profiles of molybdenum disulfide particles obtained in Examples 1 to 3 is shown in FIG. 2. As shown in FIG. 3, in all of Examples 1 to 3, the main peak (A in FIG.) at 2θ: 14˚ coincided, and also coincided with the main peaks of the 3R crystal structure and 2H crystal structure as references. In addition, in Examples 1 to 3, the peaks (B in FIG.) at 2θ: 39.5˚ and 2θ: 49.5˚ coincided, and also nearly coincided with the positions of the peaks of the 3R crystal structure and 2H crystal structure as references, but the peak shapes were different, confirming that the abundance ratio of the 3R crystal structure and 2H crystal structure and the crystallite size differed depending on the heating conditions.
[0193] In addition, in the same figure, it was confirmed that the crystal state of molybdenum disulfide particles changed due to the difference in the presence or absence of post-sintering and the post-sintering temperature, as the diffraction profiles in Examples 1 to 3 were different from each other.
[0194] Next, when waveform separation was performed on each diffraction profile of Examples 1 to 3, it was confirmed from the results in Fig. 3 that in Example 1 (sintering temperature 500°C, no post-sintering), two types of crystal structures, 3R and 2H, exist. In addition, for Example 2 (sintering temperature 500°C, post-sintering temperature 950°C) and Example 3 (sintering temperature 500°C, post-sintering temperature 1100°C), since the diffraction profile in Fig. 2 differs from that of Example 1, an extended Rietveld analysis was performed assuming that a second crystal phase of a 2H crystal structure with a small crystallite size exists in addition to the 3R and 2H crystal structures. As a result, it was confirmed that in all of Examples 2 to 3, in addition to the first crystal phases of the 3R and 2H crystal structures as crystal phases, a second crystal phase of a 2H crystal structure with an extremely small crystallite size exists (Figs. 4, 5).
[0195] Meanwhile, in Comparative Example 1, as shown in Fig. 6, the presence of a small amount of 3R crystal structure was confirmed in the commercially available molybdenum disulfide particles, but it was confirmed that almost all of them consisted of a 2H crystal structure (see Table 2). In addition, the degree of crystallization was 99.95%, and it was confirmed that all of the commercially available molybdenum disulfide particles consisted of a crystalline phase. Furthermore, the commercially available molybdenum disulfide particles' Median Glasses D 50 It was 13340nm.
[0196] Next, the relationship between the finishing firing temperature and the crystallite size in Examples 1 to 3 is shown in FIG. 7. As shown in FIG. 7, in Example 1, the crystallite size of the 2H crystal structure (crystalline phase) was 9.6 nm, the crystallite size of the 3R crystal structure (crystalline phase) was 11.8 nm, and it was found that the crystallite size of the 2H crystal structure (crystalline phase) was small, being 10 nm or less. In addition, in Example 2, the crystallite size of the 2H crystal structure (first crystal phase) was 134.9 nm, the crystallite size of the 3R crystal structure (crystalline phase) was 12.5 nm, and the crystallite size of the 2H crystal structure (second crystal phase) was 3.0 nm. In Example 3, the crystallite size of the 2H crystal structure (first crystal phase) was 118.3 nm, the crystallite size of the 3R crystal structure (crystal phase) was 36.3 nm, and the crystallite size of the 2H crystal structure (second crystal phase) was 4.3 nm. In this regard, it was found that the crystallites of the 2H crystal structure (crystal phase) grew significantly by post-sintering to become the crystallites of the 2H crystal structure (first crystal phase), and that the crystallite size of the 2H crystal structure (second crystal phase) newly generated by post-sintering was smaller than that of the 2H crystal structure (crystal phase) before post-sintering.
[0197] Next, the X-ray diffraction (XRD) profiles used to calculate the degree of crystallinity of the molybdenum disulfide particles obtained in Examples 2 and 3 are shown in FIGS. 8 and 9, respectively. In addition, the relationship between the calcination temperature and the degree of crystallinity in Examples 1 to 3 is shown in FIG. 10.
[0198] As a result of calculating the degree of crystallization from the obtained diffraction profile, the degree of crystallization was 78.7% in Example 1 (calcination temperature 500°C, no post-calcination), 89.1% in Example 2 (calcination temperature 500°C, post-calcination temperature 950°C), and 94.4% in Example 3 (calcination temperature 500°C, post-calcination temperature 1100°C). From these results, it was confirmed that the degree of crystallization increases when post-calcination is performed, and furthermore, the degree of crystallization of molybdenum disulfide particles increases when the post-calcination temperature is increased after keeping the calcination temperature the same.
[0199] Next, the relationship between the calcination temperature and the abundance of 2H crystal structure and 3R crystal structure in the crystal phase in Examples 1 to 3 is shown in FIG. 11a. As a result of calculating the abundance of each crystal structure, in Example 1, the abundance of the 2H crystal structure (crystallite size 20 nm or less) in the crystal phase was 71.5%, and the abundance of the 3R crystal structure was 28.5%. In Example 2, the abundance of the first crystal phase of the 2H crystal structure (crystallite size greater than 20 nm) in the crystal phase was 23.5%, the abundance of the 3R crystal structure was 49.3%, and the abundance of the second crystal phase of the 2H crystal structure (crystallite size 20 nm or less) was 27.2%. In addition, in Example 3, the abundance of the first crystal phase (crystallite size greater than 20 nm) of the 2H crystal structure in the crystal phase was 21.3%, the abundance of the 3R crystal structure was 57.7%, and the abundance of the second crystal phase (crystallite size less than 20 nm) of the 2H crystal structure was 21.0%. From these results, it was found that when molybdenum trioxide particles are calcined at a calcination temperature of 500°C, the abundance of the 3R crystal structure in the crystal phase can be increased to about 30%. Additionally, it was confirmed that when post-sintering is performed at 950°C, the abundance of the amorphous phase of molybdenum disulfide particles decreases to 10.9%, but the abundance of the 3R crystal structure in the crystalline phase increases, and also that when the post-sintering temperature is increased to 1100°C after the same sintering temperature, the abundance of the amorphous phase of molybdenum disulfide particles decreases to 5.6%, but the abundance of the 3R crystal structure in the crystalline phase increases.
[0200] FIG. 11b is a diagram showing the relationship between the calcination temperature and the abundance ratio of the first and second crystal phases of the 2H crystal structure, the 3R crystal structure, and the amorphous phase in the particles in Examples 1 to 3 and Comparative Example 1. As shown in FIG. 11b, it was found that in Example 1, the abundance ratio of the 3R crystal structure in the particles was significantly increased compared to Comparative Example 1. In addition, it was found that the abundance ratio of the 2H crystal structure, which consists of a crystal phase with a crystallite size of 20 nm or less, was higher than in Examples 2 and 3, and also that the abundance ratio of the amorphous phase of the molybdenum disulfide particles was higher than in Examples 2 and 3.
[0201] In Examples 2 and 3, it was found that the abundance of the amorphous phase was lower than in Example 1 but higher than in Comparative Example 1 as crystallization of the amorphous phase was promoted, and also that the abundance of the 3R crystal structure was higher than in Comparative Example 1.
[0202] In addition, in Examples 2 and 3, when the amorphous phase changed to a 2H crystal structure by post-sintering, a second crystal phase with a crystallite size of 20 nm or less was formed, and it was found that the crystallites of the 2H crystal structure with a crystallite size of 20 nm or less at 500°C sintering grew into crystallites of 100 nm or more by post-sintering (see Table 2).
[0203] Table 2 shows the results of the friction coefficients and friction evaluations calculated in Examples 1 to 3 and Comparative Example 1. From the results in Table 2, it was found that in Example 1, the abundance of the 3R crystal structure in the crystalline phase was 28.5% and the crystallite size of the 3R crystal structure was 11.8 nm, and compared to Comparative Example 1, where the abundance of the 3R crystal structure in the crystalline phase and the crystallite size were 2.9% and 88.3 nm, the friction coefficient was smaller and the friction characteristics were improved. In addition, in Example 1, the abundance of the 2H crystal structure consisting of crystallites with a crystallite size of 20 nm or less in the crystalline phase was 71.5% and the abundance of the amorphous phase in the particles was 21.3%, and compared to Examples 2 and 3, the friction coefficient was smaller and the friction characteristics were further improved.
[0204] In Examples 2 and 3, the abundance of the 3R crystal structure in the crystalline phase was 49.3% and 57.7%, respectively, and the crystallite size of the 3R crystal structure was 12.5 nm and 36.3 nm, respectively, and it was found that the friction coefficient was smaller and the friction characteristics were improved compared to Comparative Example 1. In addition, in Examples 2 and 3, the abundance of the 2H crystal structure consisting of a crystalline phase with a crystallite size of 20 nm or less and the abundance of the amorphous phase in the particle were smaller than in Example 1, but the abundance of the 3R crystal structure and the crystallite size of the 3R crystal structure were increased compared to Example 1, and as a result, it was found that a better friction coefficient was obtained compared to Comparative Example 1.
[0205] From Examples 1 to 3 and Comparative Example 1 described above, the 3R crystal structure of molybdenum disulfide particles and their crystallite size, and the medial glasses D obtained by dynamic light scattering method 50It has been demonstrated that this has a significant influence on friction characteristics. Furthermore, from the results of this embodiment, when the abundance of the 3R crystal structure of molybdenum disulfide is 20% or more and the crystallite size is 1 nm or more and 50 nm or less, the influence of the abundance of the 3R crystal structure and the crystallite size is significant, so that the media glasses D obtained by dynamic light scattering method 50 It is estimated that even with molybdenum disulfide particles exceeding 1000 nm, a good friction coefficient is obtained.
[0206] [Measurement of Friction Coefficient and Friction Evaluation of Lubricating Composition Containing Molybdenum Disulfide Particles and Organometallic Complex Particles]
[0207] [Example 4]
[0208] A lubricating composition was prepared by adding 10 parts by mass of an additive (Sanyo Gas Seisai Co., Ltd., Acroube 702), 0.08 parts by mass of molybdenum disulfide particles of Example 1, and 0.8 parts by mass of organometallic complex particles (ADEKA Co., Ltd., Sakuralube 525 (MoDTC)) to 89 parts by mass of lubricating oil (JXTG, Super Oil N32), and ultrasonically dispersing for 1 hour.
[0209] [Example 5]
[0210] A lubricating composition was prepared in the same manner as in Example 4, except that 0.08 parts by mass of molybdenum disulfide particles of Example 1 were added without adding organometallic complex particles.
[0211] [Comparative Example 2]
[0212] A lubricating composition was prepared in the same manner as in Example 4, except that neither the molybdenum disulfide particles of Example 1 nor the organometallic complex particles were added.
[0213] [Comparative Example 3]
[0214] A lubricating composition was prepared in the same manner as in Example 4, except that the molybdenum disulfide particles of Example 1 were not added, and 0.8 parts by mass of organometallic complex particles (ADEKA, Sakuralube 525 (MoDTC)) were added.
[0215] A friction and wear test was performed on a rheometer (manufactured by Anton Passa, MCR-502) equipped with a temperature-controlled dedicated stage (tribocell) for evaluating sliding characteristics. The flat portions of three SUJ2 special stainless steel cylindrical pins were tilted 45 degrees in the height direction, and the lubricating composition prepared by the above method was placed on a stage arranged evenly at 120 degrees from each other in the horizontal direction when viewed from directly above, thereby immersing the contact surface. A 1 / 2-inch SUJ2 special stainless steel sphere was then brought into contact with the pins, and a specified load was applied in the vertical direction. After standing for 5 minutes, the stage temperature was varied from 25 to 100°C, and the coefficient of friction at each temperature was obtained. The stage temperature and the temperature of the lubricating composition were kept equal, and the temperature of the lubricating composition could be controlled by varying the stage temperature. At this time, the rotation speed of the SUJ2 sphere was set to 600 rpm. The present lubricating composition was designated as Example 4, and the coefficient of friction was compared with Comparative Examples 2 to 4 shown in Table 3. "○" was marked as good if the friction coefficient was less than or equal to that of Comparative Example 2, "◎" as the best at the same temperature, and "×" as poor if it exceeded or was equal to that of Comparative Example 2. The results are shown in Table 3.
[0216] [Table 3]
[0217]
[0218] From the results of Table 3, it was found that in Example 4, the lubricating composition contains both molybdenum disulfide particles and organometallic complex particles, and the friction coefficient reduction effects of these two particles are combined, so that the friction coefficient can be significantly reduced in the temperature range of 25 to 100°C.
[0219] In addition, in Example 5 containing only molybdenum disulfide particles, the friction coefficient can be lowered over the entire temperature range compared to Comparative Example 2, and in particular, the friction coefficient was significantly lowered in the temperature range of 25 to 50°C.
[0220] Meanwhile, in Comparative Example 3, which contains only organometallic complex particles, the coefficient of friction is lower across the entire temperature range than in Comparative Example 2, which does not contain either molybdenum disulfide particles or organometallic complex particles, but compared to Example 4, the coefficient of friction is increased, particularly in the temperature range of 25 to 50°C.
[0221] Next, the results of measuring the time dependence of the friction coefficient at 75°C in Example 4 and Comparative Example 3, respectively, are shown in FIG. 12.
[0222] As shown in FIG. 12, in Example 4 containing both molybdenum disulfide particles and organometallic complex particles of Example 1, after 600 seconds, sludge caused by molybdenum dialkyldithiocarbamate (MoDTC) (manufactured by ADEKA, Sakuralube 525) used as the organometallic complex particle is generated, and the friction coefficient temporarily increases. However, the friction coefficient is lowered by the molybdenum disulfide particles, so even after the sludge is generated, a low friction coefficient equivalent to that before the sludge generation can be maintained for a long period of more than 150 seconds (approximately 20% increase), and it was found that the time dependence of the friction coefficient is good “○”.
[0223] Meanwhile, in Comparative Example 3, which contained only organometallic complex particles, after 600 seconds, sludge caused by molybdenum dialkyldithiocarbamate (MoDTC) (manufactured by ADEKA, Sakuralube 525) used as organometallic complex particles was generated, causing the friction coefficient to increase and resulting in a high load condition, making it impossible to continue the test, so the time dependence of the friction coefficient was poor "×". Explanation of the symbols
[0224] 1: Manufacturing device 2: Kiln 3: Cooling pipes 4: Recoverer 5: Exhaust pipe 6: Opening adjustment damper 7: Observation Window 8: Ventilation device 9: External cooling device
Claims
Claim 1 Molybdenum disulfide having 2H and 3R crystal structures, wherein the abundance of the said 3R crystal structure in the crystalline phase of molybdenum disulfide is 10% or more, and the crystallite size of the said 3R crystal structure calculated by extended Rietveld analysis based on the analytical formula L=Kλ / (βcosθ) using a profile obtained from powder X-ray diffraction (XRD) using Cu-Kα rays as an X-ray source is 1 nm or more and 150 nm or less, and the median lens D of the molybdenum disulfide particle obtained by dynamic light scattering method 50 Molybdenum disulfide particles having a diameter of 10 nm or more and 1000 nm or less. (In the above analysis formula, K is an instrument constant depending on the XRD optical system (incident side and detector side) and settings, L is the crystallite size [m], λ is the measured X-ray wavelength [m], β is the full width at half maximum [rad], and θ is the Bragg angle of the diffraction line [rad].) Claim 2 Molybdenum disulfide particles according to claim 1, wherein the 3R crystal structure obtained by extended Rietveld analysis is composed of a crystalline phase having a crystallite size of 5 nm or more and 50 nm or less calculated based on the analysis formula. Claim 3 Molybdenum disulfide particles according to claim 1, wherein the 2H crystal structure obtained by extended Rietveld analysis is composed of a single crystal phase consisting of crystallites having a predetermined crystallite size, and the crystallite size of the crystal phase of the 2H crystal structure is 1 nm or more and 20 nm or less. Claim 4 Molybdenum disulfide particles according to claim 3, wherein the abundance ratio of the 2H crystal structure and the 3R crystal structure in the crystal phases obtained by extended Rietveld analysis using the profile obtained from the XRD is 10:90 to 90:
10. Claim 5 Molybdenum disulfide particles according to claim 1, wherein the 2H crystal structure obtained by extended Rietveld analysis is composed of a first crystal phase having crystallites having a predetermined crystallite size and a second crystal phase having a crystallite size smaller than that of the first crystal phase, and the crystallite size of the second crystal phase of the 2H crystal structure is 1 nm or more and 20 nm or less. Claim 6 Molybdenum disulfide particles according to claim 5, wherein the abundance ratio among the first crystal phase of the 2H crystal structure, the 3R crystal structure, and the second crystal phase of the 2H crystal structure obtained by extended Rietveld analysis using the profile obtained from the XRD above is 30~10:10~70:80~15. Claim 7 Molybdenum disulfide particles according to claim 1, wherein the molybdenum disulfide particles comprise an amorphous phase, and the abundance ratio of the amorphous phase of the molybdenum disulfide particles is 5% or more. Claim 8 Molybdenum disulfide particle according to claim 1, wherein in the angular distribution function obtained from the broad-spectrum X-ray absorption microstructure (EXAFS) profile of the K absorption group of molybdenum, the ratio (I / II) of the intensity of the peak attributed to Mo-S and the intensity of the peak attributed to Mo-Mo is greater than 1.
0. Claim 9 In claim 1, the molybdenum disulfide particles have a conversion rate R from molybdenum trioxide to MoS2. C Molybdenum disulfide particles that are more than 90%. Claim 10 Molybdenum disulfide particles according to claim 1, wherein the specific surface area of the molybdenum disulfide particles, as measured by the BET method, is 10 m² / g or more. Claim 11 A lubricating composition containing molybdenum disulfide particles described in any one of claims 1 to 10, a base oil composed of one or more types of mineral oil, synthetic oil and partially synthetic oil, and additives. Claim 12 A lubricating composition according to claim 11, wherein the molybdenum disulfide particles are contained in an amount of 0.0001 mass% or more and 10 mass% or less with respect to 100 mass% of the total mass of the lubricating composition. Claim 13 A lubricating composition according to claim 11, further containing organometallic complex particles. Claim 14 A lubricating composition according to claim 13, wherein the organometallic complex particles are contained in an amount of 0.0001 mass% or more and 10 mass% or less with respect to 100 mass% of the total mass of the lubricating composition.
